Modern Human Essence in the Quran: Comparative Views of Muhammad Iqbal and Plato - Masdaudi, Muhammad Royan; Rosa Bustam, Betty Mauli (Program Studi Aqidah dan Filsafat Islam, 2024)
This study explores the essence and dimensions of modern humanity from the perspective of the Quran, focusing on the views of Muhammad Iqbal and Plato. In modern society, there is a prevailing notion that religion and science are irreconcilable entities, complicating the understanding of their relationship. This study aims to analyze the views of Iqbal and Plato on the essence and dimensions of modern humanity. The research method employed is a literature review, utilizing primary data from Iqbal's “The Reconstruction of Religious Thought in Islam” and Plato's “The Republic.” Secondary data include books, journals, essays, and other relevant sources. The findings indicate that Iqbal perceives the essence of humanity in its spiritual entity, complemented by intelligence, belief, and morality, while Plato identifies three essential elements of humanity: spirit, reason (intellect), and desire (appetite).